Macular Hole Progression after Intravitreal Bevacizumab for Hemicentral Retinal Vein Occlusion. (31st January 2012) - Nagpal, Manish; Mehta, Vikram; Nagpal, Kamal
Abstract : Macular edema secondary to retinal vein occlusion is commonly being treated with off-label intravitreal bevacizumab with good outcomes. A significant reduction in macular edema and improvement in visual acuity is seen following such a treatment with no serious adverse effects. In the reported case, a full-thickness macular hole was noticed one month after intravitreal bevacizumab for macular edema secondary to hemicentral retinal vein occlusion. On a detailed review of the pre- and postoptical coherence tomography scans, it was realized that there was a preexisting stage 2-3 macular hole which was masked by the hemorrhages and edema at the fovea and the macular hole had progressed following the injection.